The emerging role of Th1 cells in atherosclerosis and its implications for therapy - Chen, Jiaojiao; Xiang, Xuying; Nie, Lei; Guo, Xiaoqing; Zhang, Feng; Wen, Cheng; Xia, Yuanpeng; Mao, Ling (Frontiers in Immunology, 2023)
Atherosclerosis is a chronic progressive inflammatory disease of the large and medium-sized artery walls. The molecular mechanisms regulating the onset and progression of atherosclerosis remain unclear. T cells, one of the most common immune cell types in atherosclerotic plaques, are increasingly recognized as a key mediator in the pathogenesis of atherosclerosis. Th1 cells are a subset of CD4+ T helper cells of the adaptive immune system, characterized by the expression of the transcription factor T-bet and secretion of cytokines such as IFN-γ. Converging evidence shows that Th1 cells play a key role in the onset and progression of atherosclerosis. Besides, Th1 is the central mediator to orchestrate the adaptive immune system. In this review, we aim to summarize the complex role of Th1 cells in atherosclerosis and propose novel preventative and therapeutic approaches targeting Th1 cell-associated specific cytokines and receptors to prevent atherogenesis.